Analyse des pratiques langagières d'explicitation des enseignants : études de cas en aide personnalisée à l'école primaire - Éric Saillot (Université de Provence, 2014)
This text presents a descriptive and comprehensive research, based on professional didactic (Pastré, Mayen, Vergnaud, 2006, Vinatier, 2009) and analysis of the speeches-in-interaction (Kerbrat-Orecchioni, 2005), especially teachers' speech acts (Austin, 1970; Kerbrat-Orecchioni, 2008) when they try to make their pupils explain their procedures, their conceptions, or their difficulties. This type of interview can be observed in several school situations. However, since 2008, French school-teachers have been experiencing a new professional mission called « aide personnalisée » in order to help pupils in difficulties. This research aims at describing and understanding which resources are used and built by school teachers when they interview pupils to make them talk about the procedure.